2017
DOI: 10.1016/j.cub.2017.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila CRY Entrains Clocks in Body Tissues to Light and Maintains Passive Membrane Properties in a Non-clock Body Tissue Independent of Light

Abstract: Circadian (∼24 hr) clocks regulate daily rhythms in physiology, metabolism, and behavior via cell-autonomous transcriptional feedback loops. In Drosophila, the blue-light photoreceptor CRYPTOCHROME (CRY) synchronizes these feedback loops to light:dark cycles by binding to and degrading TIMELESS (TIM) protein. CRY also acts independently of TIM in Drosophila to alter potassium channel conductance in arousal neurons after light exposure, and in many animals CRY acts independently of light to repress rhythmic tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 63 publications
3
34
0
Order By: Relevance
“…S3 A and C), while MB neurons lack CRY expression (20,21). Since CRY mediates light entrainment in some pacemaker neurons and is necessary for light entrainment and clock function in peripheral tissues (19,22,23,(36)(37)(38)(39), our inability to generate an ectopic MB clock may be due to the lack of CRY. Indeed, expressing both Clk and cry in MB neurons resulted in robust PER cycling in LD (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…S3 A and C), while MB neurons lack CRY expression (20,21). Since CRY mediates light entrainment in some pacemaker neurons and is necessary for light entrainment and clock function in peripheral tissues (19,22,23,(36)(37)(38)(39), our inability to generate an ectopic MB clock may be due to the lack of CRY. Indeed, expressing both Clk and cry in MB neurons resulted in robust PER cycling in LD (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The ability of 3.0cry-Gal4driven Clk, but not MB-GS-driven Clk, to generate ectopic clocks likely results from gene expression differences in these target cell populations. One obvious difference is that 3.0cry-Gal4 presumably drives expression only in CRY-positive cells, whereas no CRY is detected in MB neurons targeted by MB-GS (19)(20)(21). To confirm that CRY is expressed in DOL cells, we used a GFP-cry transgene to mark cells that endogenously express CRY with high sensitivity (19) and found that GFP-CRY is indeed expressed in DOL cells, albeit at lower levels than in pacemaker neurons ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Furthermore, it is worth noticing that such CRY-mediated light response, involving a flavin redox-based mechanism and relying on potassium channel conductance, is independent of the circadian interaction of CRY with TIM (Fogle et al, 2011). Also, in non-neural tissues, like salivary glands, which lack a peripheral clock, CRY maintains high membrane input resistance in an Hk, Shaker, and Ether-ago-go-dependent but light-independent manner (Agrawal et al, 2017). Very interestingly, it was recently reported that lightevoked CRY membrane electrical depolarization involves W420, located in proximity to CRY FAD and important for CRYmediated depolarization in responses to not only UV and blue but also red light, at relatively low light intensity (Baik et al, 2019).…”
Section: Cry and Neuronal Activity: Uv-light Response And Arousalmentioning
confidence: 99%
“…4M-O), indicating that a functional eye is necessary for induction of sleep restriction. CRY is a UV- and blue light-sensitive protein that communicates light information to the circadian system [56][57][58] . To test whether CRY plays a role in the response to sleep opportunity restriction, we generated cry 02 :fumin double mutants.…”
Section: How Do Other Features Of Behavioral Sleep Modification In Humentioning
confidence: 99%